Understanding unmet need for family planning - Singh, Srishti; Kalhan, Meenakshi; Malik, J. S.; Jangra, Anuj; Sharma, Nitika; Singh, Srijan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Unmet need represents the gap between women’s reproductive intentions and their contraceptive behavior. There are some 225 million women in the world who want to use safe and effective family planning methods are unable to do so. Control over fertility is very important not only because of its far-reaching implications on prosperity and overall growth of the nation, but also because of its impact on the freedom of young women to lead life of their own choice. Reduction in unmet need for family planning is critical for the overall development of the society. Combination of the mutually reinforcing effects of investments in education, health and family planning programmes is needed.